Immunoregulation in the gut: success and failures in human disease. (1st May 2002) - Monteleone, I; Vavassori, P; Biancone, L; Monteleone, G; Pallone, F
Abstract : In normal conditions, human gut mucosa is infiltrated with a large number of mononuclear cells. This is a reflection of the fact that human intestine is continuously subjected to a massive stimulation by luminal antigens. This state of "physiological" inflammation is a tightly controlled phenomenon, as several mucosal cells interact to generate and maintain an appropriate local immune response. Changes in cell type number and/or function, including the release of soluble mediators, have been associated with the development of chronic inflammatory diseases, such as Crohn's disease (CD) and ulcerative colitis (UC), the two major forms of inflammatory bowel disease. Evidence also indicates that the type of inflammatory response occurring in the intestine of patients with CD differs from that in UC, and this probably reflects distinct pathways of immune activation. In CD mucosa, a Th1 response with high IL-12 and IFNγ production prevails, while in UC a humoral immunity appears to be predominant. Despite this, CD and UC share downstream inflammatory events, characterised by high levels of inflammatory cytokines, free radicals, matrix-degrading enzymes and growth factors.